La condición jurídica de los hijos de crianza en el Derecho Comparado latinoamericano - Pazmiño Chavez, Keyla Antonella (2026)
This research focuses on analyzing the legal status of foster children in the field of Latin American comparative law, with the aim of identifying regulatory convergences and divergences regarding the legal recognition of these non-biological parental bonds. The study emphasizes the Ecuadorian case, contrasting it mainly with Colombian legislation, to highlight the regulatory limitations that exist regarding the formal recognition of socioaffective filiation. It emphasizes the Ecuadorian case, contrasting it primarily with Colombian law, as it seeks to showcase existing regulations to highlight a regulatory gap regarding the formal recognition of socio-affective affiliation. Despite the Ecuadorian Constitution recognizing the diverse nature of families and the rights and interests of children, there is a legal gap in protection for foster children, who often remain rooted within the family without any specific law protecting this figure. The relevance of this regulatory gap becomes crucial in the current environment, characterized by social changes that have shifted the traditional concept of family in Latin America toward a more inclusive way of thinking centered on emotional ties. In this regard, the study conducts a comparative examination of the regulatory frameworks of different countries in the region with the aim of highlighting regulatory experiences that may guide the formulation of reform proposals for Ecuadorian law. The research carries out a formulation that responds to the legal analytical methodology and interviews with experts, concluding that the explicit inclusion of foster children as subjects of legitimate filiation is legally viable and socially necessary. It also means seeking to fully guarantee the rights of all children, as well as the search for a family model that finds its reason for being in the defense of emotional ties and children in legal justice.